Temporomandibular joint and Giant Panda’s (Ailuropoda melanoleuca) adaptation to bamboo diet - Pekka K. Vallittu (Nature Portfolio, 2021)
Abstract Here, we present new evidence that evolutionary adaptation of the Ailuripodinae lineage to bamboo diet has taken place by morphological adaptations in the masticatory system. The giant panda in the wild and in captivity removes without an exception the outer skin of all bamboo shoots, rich in abrasive and toxic compounds, by the highly adapted premolars P3 and P4. The temporomandibular joint (TMJ) allows sidewise movement of the jaw and the premolars can, in a cusp-to-cusp position, remove the poorly digestible outer skin of the bamboo before crushing the bamboo with molars. Based on the evidence presented here, we suggest that adaptation of TMJ to lateral movement for enabling cusp-to-cusp contact of premolars is the crucial evolutionary factor as which we consider the key to understand the Ailuropodinae lineage adaptive pathway to utilize the bamboo resource.